SMART CULTURAL CURATIONS: A MULTIDISCIPLINARY STUDY ON AI-ENHANCED MARKETING, TALENT RETENTION, AND FINANCIAL EFFICIENCY IN THE VISUAL ARTS TOURISM SECTOR - Kulshrestha, Ruchika; Shrivastav, Nilambara; K. Selvi; Kumar, A. Suresh; Puri, Anisha; Chandra, Saurabh (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Artificial intelligence (AI) has rapidly developed and has impacted the visual arts tourism industry greatly as it makes it possible to create new methods of marketing, talent management, and financial choices. In this paper, the author discusses the notion of smart cultural curations in the framework of a multidisciplinary approach, which combines AI-enhanced marketing, AI-guided talent management, and AI-based financial optimization. The research is based on a quantitative approach to research and utilizes a variety of AI technologies, including machine learning, data analytics, and automation, and their impacts on organizational performance and cultural tourism outcomes. Results show that AI is important in improving customer interactions and satisfaction by providing them with tailored marketing programs and also in ensuring workforce stability by using data-driven human resource management programs. Moreover, AI helps make the financial aspect more efficient by streamlining resources distribution and aiding effective decision-making. The researchers point out the mediation of the relationship between AI capabilities and tourism outcomes and organizational performance by customer engagement, customer satisfaction, and data-driven decisions. The proposal of a combined conceptual model allows the research to fill the gaps in the literature by aligning the marketing, human resource management, and financial perspectives on the topic of visual arts tourism. The research has viable implications to cultural institutions and tourism stakeholders who wish to use AI to achieve sustainable development and competitive edge.